Loss-of-function mutations in TNFAIP3 leading to A20 haploinsufficiency cause an early-onset autoinflammatory disease - Zhou, Qing; Wang, Hongying; Schwartz, Daniella M; Stoffels, Monique; Park, Yong Hwan; Zhang, Yuan; Yang, Dan; Demirkaya, Erkan; Takeuchi, Masaki; Tsai, Wanxia Li; Lyons, Jonathan J; Yu, Xiaomin; et al. (Nature genetics, 2016)
Ivona Aksentijevich and colleagues identify heterozygous loss-of-function mutations in TNFAIP3 (encoding A20) in six unrelated families with early-onset systemic inflammation. Affected individuals exhibit increased expression of NF-κB–mediated proinflammatory cytokines, consistent with the established role of A20 as a potent inhibitor of the NF-κB signaling pathway. Systemic autoinflammatory diseases are driven by abnormal activation of innate immunity 1 . Herein we describe a new disease caused by high-penetrance heterozygous germline mutations in TNFAIP3 , which encodes the NF-κB regulatory protein A20, in six unrelated families with early-onset systemic inflammation. The disorder resembles Behçet's disease, which is typically considered a polygenic disorder with onset in early adulthood 2 . A20 is a potent inhibitor of the NF-κB signaling pathway 3 . Mutant, truncated A20 proteins are likely to act through haploinsufficiency because they do not exert a dominant-negative effect in overexpression experiments. Patient-derived cells show increased degradation of IκBα and nuclear translocation of the NF-κB p65 subunit together with increased expression of NF-κB–mediated proinflammatory cytokines. A20 restricts NF-κB signals via its deubiquitinase activity. In cells expressing mutant A20 protein, there is defective removal of Lys63-linked ubiquitin from TRAF6, NEMO and RIP1 after stimulation with tumor necrosis factor (TNF). NF-κB–dependent proinflammatory cytokines are potential therapeutic targets for the patients with this disease.